Recent progress in perovskite solar cells: the perovskite layer - Dai, Xianfeng; Xu, Ke; Wei, Fanan (Beilstein Journal of Nanotechnology, 2020)
Perovskite solar cells (PSCs) are set to be game changing components in next-generation photovoltaic technology due to their high efficiency and low cost. In this article, recent progress in the development of perovskite layers, which are the basis of PSCs, is reviewed. Achievements in the fabrication of high-quality perovskite films by various methods and techniques are introduced. The reported works demonstrate that the power conversion efficiency of the perovskite layers depends largely on their morphology and the crystalline quality. Furthermore, recent achievements concerning the scalability of perovskite films are presented. These developments aim at manufacturing large-scale perovskite solar modules at high speed. Moreover, it is shown that the development of low-dimensional perovskites plays an important role in improving the long-term ambient stability of PSCs. Finally, these latest advancements can enhance the competitiveness of PSCs in photovoltaics, paving the way for their commercialization. In the closing section of this review, some future critical challenges are outlined, and the prospect of commercialization of PSCs is presented.
Keywords: coating techniques; perovskite layer; perovskite solar cells (PSCs); perovskite structure; photovoltaic technology; scalability